Pengaruh Faktor Demografi dan Lingkungan Sosial Terhadap Keputusan Pembelian Dimediasi Oleh Perilaku Membaca Atribut Label. - Widyastuti, Ni Putu Ayu; Widagda K., I G.N. Jaya Agung (E-Jurnal Manajemen, 2014)
This study aims to determine the influence of demographic factors and social environment on purchasing decisions mediated by reading the label attribute behavior with a case study UHT milk of Ultrajaya brand products are located in the city of Denpasar. This study took the 100 respondents with purposive sampling as sampling. Collecting data in this study used a questionnaire with data analysis techniques using path analysis.The results showed that the demographic factors and the social environment can direct influence over the purchase decision, while demographic factors and the social environment is not entirely mediated influence on purchase decisions by reading the label attribute behavior. The test results showed that social environmental factors can be positive and significant influence on purchasing decisions mediated by behavioral attributes read the label.
Keywords: : demographic factors, social environment, read the label attribute, the purchase decision.